A study of the mechanical response of polycrystalline ice subjected to dynamic tension loading using the spalling test technique. (October 2019) - Saletti, Dominique; Georges, David; Gouy, Victor; Montagnat, Maurine; Forquin, Pascal
Highlights: The spalling test technique is conducted to study the dynamic tensile strength of polycrystalline ice. The results show the sensitivity of the tensile strength to the applied strain rate (from 41 s − 1 to 271 s − 1 ). Three indicators are proposed to assess the results based on an optical analysis, a measurement of the wave speed and an analysis of the transmitted pulse. An increase of the cracking density with the strain rate is observed. Abstract: Polycrystalline ice has been extensively investigated during the last decades regarding its mechanical behaviour for quasi-static loadings. Conversely, only few studies can be found on its dynamic behaviour and scientists suffer from a lack of experimental observation to develop relevant modelling at high strain-rate ranges. Dynamic experiments have already been conducted in compression mode using Hopkinson bar set-up. Regarding tension, experimental observations and measurements are scarce. The literature gives only approximated strength values. The knowledge of the latter is essential to design structures that may experience ice impact. The present study aims at providing the first reproducible experimental data of the tensile strength of polycrystalline ice subjected to dynamic tensile loading. To do so, a spalling test technique has been used for the first time on ice to apply tensile loading at strain-rates from 41 s − 1 to 271 s − 1 . The experimental results show that the tensile strength is sensitive to the applied strain-rate, evolving from 1.9 MPa to 16.3 MPa for the highest applied loading rate.